Visualisasi Interaktif Tanaman Obat Tradisional Berbasis Augmented Reality Sebagai Media Edukasi - Apriliani K. Belalawe; Remerta N. Naatonis; Erna R. Nubatonis (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
Knowledge of traditional medicinal plants is still mostly passed down from generation to generation and has not been properly documented digitally, resulting in low interest among younger generations in learning about traditional medicinal plants. This study aims to design and develop an interactive educational media based on Augmented Reality (AR) to help the public understand information about traditional medicinal plants in a more engaging and interactive way. The method used in this study is the Multimedia Development Life Cycle (MDLC), which consists of the stages of concept, design, material collection, assembly, testing, and distribution. The system was developed using ZapWorks Studio for AR implementation and Blender for creating 3D models of medicinal plants. The results of this study indicate that the AR-based educational media is capable of displaying visualizations of traditional medicinal plants in the form of three-dimensional objects along with information on their benefits and interactive 3D animation of the preparation process. This system can be used as an engaging learning media and support the preservation of traditional medicinal plant knowledge in the digital era.